Rancang Bangun Sistem Informasi Penyewaan Kos Putri Di Kelurahan Onekore - grasiana jinda; Yoseph D. Da Khwuta; Elvira Esperanza Sala (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Abstract Boarding house is one of the places that provides lodging services or semetara residence consisting of several rooms and each room has facilities offered or provided and also has a price that has been determined by the owner of their respective boarding house. A boarding house tenant is an agreement with one party binding itself to give to the other party, for a certain time at the agreed and agreed price. The purpose of this study is to build a boarding room rental information system that can provide information for boarding room rentals according to the criteria and can book boarding rooms without having to go to the location using the RAD (Rapid Application Development) method. RAD is a software process model that emphasizes a short life development cycle. In this study, the application of the RAD method will be divided into three stages including design, system design and implementation. The final result expected from this study is that the existence of this boarding room tenant information system will make it easier for residents generally in the central ende district of ende regency to carry out the process of searching and booking boarding rooms Keywords— information system, Rapid Application Development, boarding house, tenant boarding house, black box testing